A single machine-based scheduling optimisation model integrated with preventive maintenance policy for maximising the availability. (3rd April 2012) - Pan, Ershun; Liao, Wenzhu; Xi, Lifeng
This paper proposes a scheduling optimisation model integrated with preventive maintenance policy to solve a single machine scheduling problem. In the previous scheduling models, machine degradation is usually ignored. However, in reality, machine will fail due to degradation, which interrupts manufacturing processes. In order to keep smooth production and reduce unexpected waste, preventive maintenance is thus considered into the production scheduling model with the aim to maximise the machine availability. In this scheduling optimisation model, system's failure rate is considered to increase with increased usage and age subjected to machine degradation and an effective age is proposed to describe machine's real condition. Finally, a case study is given, and then the results obtained under different maintenance policies are discussed. The computational results show this proposed scheduling optimisation model integrated with preventive maintenance policy has a better performance, which proves its efficiency.